ELEMENTARY IN THE CLASSROOMS NEW PEDAGOGICAL TECHNOLOGIES USING LESSON TEACHING (American Journal of Interdisciplinary Research and Development, 2025)
In the article elementary classes to their student's modern pedagogical technologies based on education of giving advantages, pedagogical the process effective organization to do, students independent thinking and creative approach develop issues illuminated.